ANALISIS KESESUAIAN INSTRUMEN PENGKAJIAN KESEHATAN MULUT ORAL HEALTH ASSESMENT TOOL (OHAT) DAN ORAL ASSESMENT SCALE (OAS) PADA PASIEN CRITICAL CARE - Ayu, Yanu; Karunia Estri, Arimbi; Dede Yoshima Nekada, Cornelia (Yayasan Healing and Healthcare Education, 2025)
Oral hygiene is very important to prevent infection in patients in the ICU, especially those using ventilators. The mouth's natural cleansing mechanism can be disrupted, increasing the risk of ventilator-associated pneumonia (VAP) due to microorganisms that develop in the oropharynx and spread to the airways within 48 hours.